(untitled) (American Journal of Humanities and Social Sciences, 2015)
Food has always been a means of survival as its nutrient function for the survival of the body system, especially infant that need a proper building of their body system. The first, the best and the most complete nutrient a baby needs is the Breast milk. The act and practice of exclusive Breastfeeding have an advance impact on the child, the mother and the society at large, as the study examines the social analysis of the benefit and hindrances of exclusive breastfeeding among the Muslims in selected communities in Edo State, Nigeria. Social Action theory was used to buttress the benefit of exclusive breastfeeding, 150 Muslim women were interviewed with the aid of a structured questionnaire and an in-depth interview administered face-to face to the respondents. A cluster and purposive sampling technique was utilized and the findings analyzed with the use of Statistical Package for Social Sciences (SPSS) 20.0 version. It was discovered that one of the hindrances to exclusive breastfeeding is caused by the health condition f the mother among others, inversely the benefit too numerous one off which is making the children/infant brilliant and healthy. Hence it is recommended that Exclusive Breastfeeding should be encouraged because of its medical/health benefit to both mother and child in both the national and international level for the realization of the Millennium Development Goal strategy by 2015.